Composite electrolyte containing gradient salt concentration, preparation method, application and lithium battery thereof

By using composite electrolytes containing gradient salt concentration in lithium batteries, the problem that electrolytes in the prior art is difficult to have good electrochemical, mechanical and safety performance at the same time, and the efficient and safe electrochemical performance of lithium batteries is achieved.

CN114976238BActive Publication Date: 2025-03-21SHANGHAI ELECTRICGROUP CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210567710.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-05-23
Publication Date
2025-03-21
Estimated Expiration
2042-05-23

AI Technical Summary

Technical Problem

In existing lithium batteries, solid-liquid mixed electrolytes formed by polymer-lithium salt-organic solvents are difficult to have good electrochemical, mechanical and safety properties at the same time.

Method used

A composite electrolyte containing gradient salt concentration is used, which consists of multi-layer electrolyte layer units. The lithium salt concentration in each unit increases, combining the ratio of polymer and organic solvents to optimize the interface performance between the electrolyte and the electrode material.

Benefits of technology

It achieves both good electrochemical, mechanical and safety performance of electrolytes in lithium batteries, ensuring the cycling performance, rate performance and safety of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003658144100000121
    Figure BDA0003658144100000121
Patent Text Reader

Abstract

The present invention discloses a composite electrolyte containing a gradient salt concentration, a preparation method, an application, and a lithium battery. The composite electrolyte comprises a first electrolyte layer, a second electrolyte layer, and a third electrolyte layer. The second electrolyte layer is located between the first and third electrolyte layers. The first and third electrolyte layers respectively comprise N and M sequentially stacked electrolyte layer units. The electrolyte layer units in the first and third electrolyte layers are respectively recorded as A1 to A2 according to the distance from each electrolyte layer unit to the second electrolyte layer from far to near. N and A'1 to A' M The electrolyte layer units each independently include a first polymer, a first organic solvent and a first lithium salt, and the concentration of the first lithium salt in each electrolyte layer unit is from A1 to A N and from A'1 to A' M The second electrolyte layer contains a second polymer, a second organic solvent and a second lithium salt. The composite electrolyte of the present invention has good battery electrochemical performance, mechanical performance and safety.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a composite electrolyte containing gradient salt concentration, a preparation method, an application and a lithium battery thereof. Background Art

[0002] Lithium-ion batteries are a new type of battery developed after lead-acid batteries, nickel-cadmium batteries and nickel-hydrogen batteries. Compared with traditional batteries, lithium-ion batteries have the advantages of high conversion efficiency, recyclability, cleanliness and zero emissions, as well as high energy density, long cycle life and zero memory effect, making them an indispensable part of daily life while facilitating people's lives. However, people's demand for higher energy density and safety of lithium-ion batteries has also increased.

[0003] Since there is a negative correlation between the energy density and safety of the positive and negative electrode materials of lithium batteries, the main reason for this phenomenon is that the materials with high energy density are more active and easy to react, while the electrolytes in contact with them - currently commercialized mainly in the form of organic solvents + lithium salts - contain flammable and explosive organic solvents. This makes the entire battery system extremely unstable when disturbed by external factors, and prone to safety accidents such as combustion and explosion.

[0004] In order to improve energy density while avoiding safety accidents, the introduction of polymer electrolytes into lithium batteries with high nickel content ternary materials as positive electrodes can be adopted, that is, replacing the original electrolyte with polymer + lithium salt + organic solvent, thereby avoiding safety accidents caused by the reaction between the electrolyte and the electrode material. In the solid-liquid mixed electrolyte formed by polymer-lithium salt-organic solvent, if the polymer ratio is high, the ionic conductivity of the electrolyte is low and the compatibility with the electrode interface is poor, and the battery cycle performance and rate performance will be reduced; when the ratio of organic solvent-lithium salt is high, the mechanical properties of the electrolyte membrane are poor, it is difficult to process, and it is easy to leak, and the safety is reduced. Summary of the invention

[0005] The technical problem to be solved by the present invention is to overcome the defects of the solid-liquid mixed electrolyte formed by polymer-lithium salt-organic solvent in the prior art that it is difficult to simultaneously have good battery electrochemical properties (such as the ionic conductivity of the electrolyte, compatibility with the electrode interface, battery cycle performance and rate performance), mechanical properties and safety, and to provide a composite electrolyte containing a gradient salt concentration and its preparation method, application, and lithium battery.

[0006] The present invention solves the above technical problems through the following technical solutions:

[0007] A composite electrolyte containing a gradient salt concentration, comprising a first electrolyte layer, a second electrolyte layer, and a third electrolyte layer, wherein:

[0008] The second electrolyte layer is located between the first electrolyte layer and the third electrolyte layer,

[0009] The first electrolyte layer includes N electrolyte layer units stacked in sequence, and the third electrolyte layer includes M electrolyte layer units stacked in sequence, wherein N and M are both natural numbers and integers, and N≥2, M≥2;

[0010] According to the distance from each electrolyte layer unit to the second electrolyte layer from far to near, the N sequentially stacked electrolyte layer units in the first electrolyte layer are recorded as A1, A2, ...A N-1 , A N , the M sequentially stacked electrolyte layer units in the third electrolyte layer are denoted as A'1, A'2, ...A' M-1 , A' M ; Wherein, A1 and A'1 are respectively located in the outermost layer of the gradient salt concentration composite electrolyte;

[0011] The components of the electrolyte layer units independently include a first polymer, a first organic solvent and a first lithium salt, and the concentration of the first lithium salt in each electrolyte layer unit is from A1 to A N and from A'1 to A' M All increase in sequence; wherein, the concentration of the first lithium salt in A1 and A'1 is 0.9-1.1 mol / L, and in the electrolyte layer units other than A1 and A'1, the concentration of the first lithium salt is 1-5 mol / L, and the concentration of the first lithium salt refers to the concentration of the first lithium salt relative to the first organic solvent;

[0012] The ratio of the sum of the mass of the first lithium salt and the first organic solvent to the mass of the first polymer is (0.8-1.1):1;

[0013] The components of the second electrolyte layer include a second polymer, a second organic solvent and a second lithium salt; wherein the sum of the masses of the second lithium salt and the second polymer accounts for 10-30%, % refers to the percentage of the sum of the masses of the second lithium salt and the second polymer to the mass of the second electrolyte layer, and the mass ratio of the second polymer to the second lithium salt is (3-4):1.

[0014] In the present invention, generally, the concentration (mol / L) of the first lithium salt refers to the ratio of the number of moles of the first lithium salt to the volume of the first organic solvent, wherein the first lithium salt is dissolved in the first organic solvent and the volume occupied by the first lithium salt is negligible.

[0015] In the present invention, preferably, the types of the first lithium salt, the first polymer and the first organic solvent of each electrolyte layer unit are respectively the same as the types of the first lithium salt, the first polymer and the first organic solvent in other electrolyte layer units.

[0016] In the present invention, preferably, the thickness of each electrolyte layer unit is less than 100 μm.

[0017] In the present invention, preferably, the types of the first polymer and the second polymer are independently selected from one or more of polyethylene oxide, polyvinylidene fluoride, polyacrylonitrile and polymethyl methacrylate, more preferably, selected from one or more of polyethylene oxide, polyvinylidene fluoride and polyacrylonitrile, such as polyethylene oxide or polyacrylonitrile.

[0018] The number average molecular weight of the polyethylene oxide is preferably 50,000 to 3,000,000, more preferably 100,000 to 3,000,000, and even more preferably 300,000 to 1,000,000.

[0019] The number average molecular weight of the polyvinylidene fluoride is preferably 10,000 to 80,000, more preferably 20,000 to 50,000.

[0020] The number average molecular weight of the polyacrylonitrile is preferably 8,000 to 50,000, more preferably 10,000 to 30,000.

[0021] Wherein, the number average molecular weight of the polymethyl methacrylate is preferably 25,000 to 200,000.

[0022] In the present invention, preferably, the first polymer and the second polymer are of the same type.

[0023] In the present invention, preferably, the type of the first organic solvent is selected from one or more of cyclic carbonates, chain carbonates, ethers and sulfones, such as cyclic carbonates and ethers.

[0024] Preferably, the cyclic carbonates include but are not limited to a combination of one or more of ethylene carbonate, propylene carbonate and γ-butyrolactone, such as propylene carbonate.

[0025] Among them, preferably, the chain carbonates include but are not limited to one or more combinations of ethyl methyl carbonate, dimethyl carbonate, diethyl carbonate, methyl formate, ethyl formate, methyl acetate, ethyl acetate, n-propyl acetate, methyl propionate, ethyl propionate, n-propyl propionate, methyl butyrate and ethyl butyrate.

[0026] Among them, preferably, the ether is selected from one or more combinations of ethylene glycol dimethyl ether, ethylene glycol diethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether or tetraethylene glycol dimethyl ether, 1,3-dioxolane, 1,3-dioxane, 1,4-dioxane, tetrahydrofuran and 2-methyltetrahydrofuran, such as ethylene glycol dimethyl ether or ethylene glycol diethyl ether.

[0027] Preferably, the sulfone is selected from one or more of dimethyl sulfoxide, sulfolane, and dimethyl sulfone.

[0028] Among them, preferably, the first organic solvent is "propylene carbonate and ethylene glycol dimethyl ether" or "propylene carbonate and ethylene glycol diethyl ether".

[0029] When the number of the first organic solvents is two or more, the mass ratio between the different types of organic solvents may be any mass ratio.

[0030] When the first organic solvent includes two organic solvents, the mass ratio of the two organic solvents may be (4-5):(5-6), for example, 4:6 or 5:5.

[0031] In a preferred embodiment of the present invention, the first organic solvent is propylene carbonate and ethylene glycol dimethyl ether in a mass ratio of 4:6.

[0032] In another preferred embodiment of the present invention, the first organic solvent is propylene carbonate and ethylene glycol diethyl ether in a mass ratio of 5:5.

[0033] In the present invention, the first lithium salt and the second lithium salt are represented by the chemical formula LiY. Preferably, Y - Including but not limited to: PF6 - 、CH3SO3 - 、SCN - 、BF4 - 、ClO4 - 、NO3 - , [O3SCF2CF3] - 、AsF6 - 、AlCl4 - 、(CF3SO2)2N - (LiTFSI for short), (FSO2)2N - (LiFSI for short), CF3SO3 - 、B(OC2O2)2 - (LiBOB for short), (OC2O2)F2B - (LiODFB for short), (C3F6SO2)(FSO2)N -(LiFNFSI for short) or Li[(CF3SO2)(n-C4F9SO2)N] (LiTNFSI for short).

[0034] In the present invention, preferably, the first lithium salt and the second lithium salt are of the same type.

[0035] In the present invention, preferably, the first lithium salt and the second lithium salt are both (CF3SO2)2N - (LiTFSI for short).

[0036] In the present invention, preferably, the concentration of the first lithium salt in A1 and A'1 is 1M.

[0037] In the present invention, preferably, in the electrolyte layer units other than A1 and A'1, the concentration of the first lithium salt is independently 1-2M, for example, 1.2, 1.3 or 1.5M.

[0038] In the present invention, there is no special requirement for the difference in the concentration of the first lithium salt between each electrolyte layer unit corresponding to the sequential increase, for example, from A1 to A N The difference in concentration of the first lithium salt between each electrolyte layer unit may be the same or different.

[0039] Among them, preferably, from A1 to A N or from A'1 to A' M , the difference in concentration of the first lithium salt between each electrolyte layer unit is independently selected from 0.1, 0.2 or 0.5 mol / L.

[0040] In the present invention, preferably, N in the first electrolyte layer and M in the third electrolyte layer have the same value.

[0041] In the present invention, preferably, when N and M have the same value, A in the first electrolyte layer N and A' in the third electrolyte layer M Exactly the same, A N-1 and A' M-1 Completely the same, and so on. For example, when N and M are both 2, A1 and A'1 are completely the same, and A2 and A'2 are completely the same. Here, completely the same means that the composition of each component is completely the same.

[0042] In the present invention, preferably, the values ​​of N and M are independently 2-4, for example, N and M are both 2 or 3.

[0043] In a preferred embodiment of the present invention, the values ​​of N and M are both 2, the concentration of the first lithium salt in A1 and A'1 is both 1 mol / L; the concentration of the first lithium salt in A2 and A'2 is both 1.5 mol / L.

[0044] More preferably, in A1, A'1, A2 and A'2, the first lithium salt is LiTFSI, the first polymer is polyethylene oxide with a number average molecular weight of 50,000, and the first organic solvent is a mixed solvent of propylene carbonate and ethylene glycol dimethyl ether in a mass ratio of 4:6.

[0045] In another preferred embodiment of the present invention, the values ​​of N and M are 3, the concentration of the first lithium salt in A1 and A'1 is 1 mol / L; the concentration of the first lithium salt in A2 and A'2 is 1.2 mol / L; the concentration of the first lithium salt in A3 and A'3 is 1.3 mol / L.

[0046] More preferably, in A1 to A3 and A'1 to A'3, the first lithium salt is LiTFSI, the first polymer is polyacrylonitrile with a number average molecular weight of 10,000, and the first organic solvent is a mixed solvent of propylene carbonate and ethylene glycol diethyl ether in a mass ratio of 5:5.

[0047] In the present invention, in the first electrolyte layer, preferably, the ratio of "the sum of the masses of the first lithium salt and the first organic solvent" to the mass of the first polymer is (0.9-1.1):1, for example 1:1.

[0048] In the present invention, in the second electrolyte layer, preferably, the sum of the masses of the second lithium salt and the second polymer accounts for 15-30%, such as 20% or 25%, wherein % refers to the percentage of the sum of the masses of the second lithium salt and the second polymer in the mass of the second electrolyte layer.

[0049] In the present invention, in the second electrolyte layer, preferably, the mass ratio of the second polymer to the second lithium salt is 3:1 or 4:1.

[0050] In the present invention, in the second electrolyte layer, preferably, the second organic solvent can be a conventional organic solvent in the art, such as N-methylpyrrolidone, for dissolving lithium salt and polymer.

[0051] In the present invention, there is no specific requirement for the amount of the second organic solvent in the second electrolyte layer, as long as it can dissolve the lithium salt and the polymer.

[0052] The present invention also provides a method for preparing a composite electrolyte containing a gradient salt concentration, which comprises the following steps:

[0053] Mix the mixture B1, B2, ...B N-1 , B N , C, B' M , B' M-1 , ...B'2, B'1, are sequentially coated on the base layer; wherein,

[0054] The mixed solutions B1 and B'1 respectively include a first lithium salt, a first organic solvent and a first polymer, wherein the concentration of the first lithium salt is 0.9-1.1 mol / L,

[0055] Mixture B2, ...B N-1 , B N The difference between the mixed solution B1 and the mixed solution B2 is that the concentration of the first lithium salt is different and the concentration of the first lithium salt is different from that of the mixed solution B1. N The concentration of lithium salt is independently 1-5 mol / L.

[0056] Mixture B'2, ...B' M-1 , B' M The difference between the mixed solution B'1 and B' is that the concentration of lithium salt is different and the concentration of lithium salt is different from B'1 to B' M The concentration of lithium salt is increased successively, and each of them is independently 1-5 mol / L;

[0057] Said N and M are both natural numbers and integers, and N≥2, M≥2;

[0058] The concentration of the first lithium salt is 1-5 mol / L, and the concentration of the first lithium salt refers to the concentration of the first lithium salt relative to the first organic solvent;

[0059] The ratio of the sum of the mass of the first lithium salt and the first organic solvent to the mass of the first polymer is (0.8-1.1):1;

[0060] The mixed solution C includes a second lithium salt, a second organic solvent and a second polymer;

[0061] The sum of the masses of the second lithium salt and the second polymer accounts for 10-30%, % refers to the percentage of the sum of the masses of the second lithium salt and the second polymer in the mass of the mixed solution C, and the mass ratio of the second polymer to the second lithium salt is (3-4):1.

[0062] In the present invention, preferably, the coating thickness each time is less than 100 μm.

[0063] In the present invention, preferably, the types of the first lithium salt, the first organic solvent and the first polymer are as described above.

[0064] In the present invention, preferably, the types of the second lithium salt, the second organic solvent and the second polymer are as described above.

[0065] In the present invention, preferably, the concentration of the first lithium salt in the mixed solutions B1 and B'1 is 1 mol / L.

[0066] In the present invention, preferably, the mixed solution B2 to B N Mixture B'2 to B'M In the method, the concentration of the first lithium salt is independently 1-2 mol / L, such as 1.2, 1.3 or 1.5 mol / L.

[0067] In the present invention, preferably, from B1 to B N or from B'1 to B' N There is no special requirement for the difference in concentration of the first lithium salt between each mixed solution corresponding to the sequential increase, and they can be the same or different.

[0068] For example, the difference in the concentration of the first lithium salt corresponding to the sequential increase is independently selected from 0.1, 0.2 or 0.5 mol / L.

[0069] In the present invention, preferably, when N and M have the same value, B in the first electrolyte layer N and B' in the third electrolyte layer M Exactly the same, B N-1 and B' M-1 Exactly the same, and so on. For example, when N and M are both 2, B1 and B'1 are exactly the same, and B2 and B'2 are exactly the same. Exactly the same means that the composition of each component is exactly the same.

[0070] In the present invention, preferably, the values ​​of N and M are independently 2-4, for example, independently 2 or 3.

[0071] In a preferred embodiment of the present invention, the values ​​of N and M are both 2, the concentration of the first lithium salt in B1 and B'1 is both 1 mol / L; the concentration of the first lithium salt in B2 and B'2 is both 1.5 mol / L.

[0072] More preferably, in B1, B'1, B2 and B'2, the first lithium salt is LiTFSI, the first polymer is polyethylene oxide with a number average molecular weight of 50,000, and the first organic solvent is a mixed solvent of propylene carbonate and ethylene glycol dimethyl ether in a mass ratio of 4:6.

[0073] In another preferred embodiment of the present invention, N and M are both 3, the concentration of the first lithium salt in B1 and B'1 is 1 mol / L; the concentration of the first lithium salt in B2 and B'2 is 1.2 mol / L; the concentration of the first lithium salt in B3 and B'2 is 1.3 mol / L.

[0074] More preferably, in B1 to B3 and B'3 to B'3, the first lithium salt is LiTFSI, the first polymer is polyacrylonitrile with a number average molecular weight of 10,000, and the first organic solvent is a mixed solvent of propylene carbonate and ethylene glycol diethyl ether in a mass ratio of 5:5.

[0075] In the present invention, preferably, the ratio of "the sum of the masses of the first lithium salt and the first organic solvent" to the mass of the first polymer is (0.9-1.1):1, for example 1:1.

[0076] In the present invention, preferably, the preparation method of the mixed solution B1 comprises the following steps: dissolving the first lithium salt in the first organic solvent and then mixing with the first polymer. N and mixed solutions B'1 to B' M The preparation method is similar.

[0077] The mixing operation may be a conventional mixing operation in the art, and the mixing may be uniform, for example, a stirring step may be generally included.

[0078] The stirring can be carried out under conventional conditions in the art, for example, at room temperature.

[0079] The stirring time may be conventional in the art, for example 1 hour.

[0080] Preferably, the sum of the masses of the second lithium salt and the second polymer in the mixed solution C accounts for 15-30%, for example 20% or 25%, wherein % refers to the percentage of the sum of the masses of the second lithium salt and the second polymer in the mass of the mixed solution C.

[0081] Preferably, the mass ratio of the second polymer to the second lithium salt in the mixed solution C is 3:1 or 4:1.

[0082] In the present invention, the base layer may be a conventional electrode plate in the art, such as a negative electrode plate.

[0083] The negative electrode plate may be a conventional negative electrode plate in the art, such as graphite.

[0084] In the present invention, preferably, curing is performed after the coating.

[0085] The curing can be carried out under an inert atmosphere according to the conventional art, such as argon.

[0086] The curing may generally include thermal curing, such as baking.

[0087] The thermal curing temperature may be a conventional temperature in the art, such as 60 or 80°C.

[0088] The heat curing time may be a conventional time in the art, such as 20 minutes.

[0089] In the present invention, preferably, the mixed solution C is coated at 75-85°C, for example 80°C.

[0090] The present invention also provides a composite electrolyte containing a gradient salt concentration, which is prepared by the method for preparing a composite electrolyte containing a gradient salt concentration as described above.

[0091] The present invention also provides a battery core, which comprises a positive electrode, a negative electrode, and the composite electrolyte containing a gradient salt concentration as described above.

[0092] In the present invention, according to the conventional art, in the battery cell, the positions of the negative electrode and the positive electrode overlap with each other to form a laminate, and the composite electrolyte containing a gradient salt concentration is located between the negative electrode and the positive electrode.

[0093] The present invention also provides an application of the composite electrolyte containing gradient salt concentration as mentioned above in a battery.

[0094] The present invention also provides a lithium battery, which comprises the composite electrolyte containing gradient salt concentration as described above.

[0095] In the present invention, the lithium battery may further include a positive electrode and a negative electrode according to the conventional art.

[0096] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.

[0097] The reagents and raw materials used in the present invention are commercially available.

[0098] The positive and progressive effects of the present invention are:

[0099] The present invention prepares a composite electrolyte by adopting gradient salt concentration, polymer and organic solvent, optimizes the interface performance between the electrolyte and the electrode material, maintains good cycle and rate performance, and can pass the puncture test and heating test of the lithium battery. The composite electrolyte has good electrochemical performance, mechanical performance and safety performance. DETAILED DESCRIPTION

[0100] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0101] Example 1

[0102] The preparation of the composite electrolyte containing a gradient salt concentration, the specific steps are as follows:

[0103] (1) Dissolve 2.87 g of LiTFSI in 10 mL of a mixed solvent of propylene carbonate and ethylene glycol dimethyl ether (mass ratio of 4:6) and stir well;

[0104] (2) 1 g of the solution obtained in (1) (lithium salt concentration is 1 M) was mixed with 1 g of polyethylene oxide with a number average molecular weight of 50,000, and stirred at room temperature for 1 h. This was recorded as electrolyte 1.

[0105] (3) 4.305 g of LiTFSI was dissolved in 10 mL of a mixed solvent of propylene carbonate and ethylene glycol dimethyl ether (mass ratio of 4:6) and stirred evenly;

[0106] (4) 1 g of the solution obtained in (3) (lithium salt concentration is 1.5 M) was mixed with 1 g of polyethylene oxide with a number average molecular weight of 50,000, and stirred at room temperature for 1 h. This was recorded as electrolyte 2.

[0107] (5) Using N-methylpyrrolidone as a solvent (there is no specific requirement for the amount of the solvent, and the solvent is added until the lithium salt and the polymer are dissolved), add 0.2 g of LiTFSI and 0.8 g of polyethylene oxide with a number average molecular weight of 50,000, stir and dissolve evenly, and record it as an electrolyte solution; wherein the sum of the mass of the lithium salt and the polyethylene oxide accounts for 20% of the mass of the electrolyte solution;

[0108] (6) Electrolytes 1 and 2 are sequentially applied to the negative electrode sheet, and after each application, the electrolyte is baked at 60° C. for 20 min in an argon atmosphere before applying the next electrolyte; the coating thickness of each layer after application and baking is less than 100 μm;

[0109] (7) Heat the electrolyte solution to 80°C, apply it on electrolyte 2, and bake it at 80°C for 20 min in an argon atmosphere;

[0110] (8) Repeat step (6) in the order of electrolytes 2 and 1 to prepare a composite electrolyte containing a gradient salt concentration.

[0111] Preparation of the battery:

[0112] (9) The negative electrode sheet (graphite) coated with electrolyte obtained in step (8) and the positive electrode sheet (5 series ternary positive electrode material) are stacked to form a battery cell;

[0113] (10) packaging the battery cell obtained in step (9);

[0114] (11) The battery obtained in step (10) is formed and finally sealed.

[0115] The prepared battery was tested, with a 1C 200 cycle capacity retention rate of 99%, a discharge capacity at 3C of 90% of that at 1C, and passed the national standard GB / T 31485-2015 puncture test and heating test.

[0116] Example 2

[0117] The preparation of the composite electrolyte containing a gradient salt concentration, the specific steps are as follows:

[0118] (1) Dissolve 2.87 g of LiTFSI in 10 mL of a mixed solvent of propylene carbonate and ethylene glycol diethyl ether (mass ratio of 5:5) and stir well;

[0119] (2) 0.8 g of the solution obtained in (1) (lithium salt concentration 1 M) was mixed with 1 g of polyacrylonitrile with a number average molecular weight of 10,000, and stirred at room temperature for 1 h, which was recorded as electrolyte 1; the coating thickness of each layer after coating and baking was less than 100 μm;

[0120] (3) Dissolve 3.444 g of LiTFSI in 10 mL of a mixed solvent of propylene carbonate and ethylene glycol diethyl ether (mass ratio of 5:5) and stir evenly;

[0121] (4) 0.8 g of the solution obtained in (3) (lithium salt concentration is 1.2 M) was mixed with 1 g of polyacrylonitrile with a number average molecular weight of 10,000, and stirred at room temperature for 1 h. This was recorded as electrolyte 2.

[0122] (5) Dissolve 3.731 g of LiTFSI in 10 mL of a mixed solvent of propylene carbonate and ethylene glycol diethyl ether (mass ratio of 5:5) and stir well;

[0123] (6) 1.0 g of the solution obtained in (5) (lithium salt concentration is 1.3 M) was mixed with 1 g of polyacrylonitrile with a number average molecular weight of 10,000, and stirred at room temperature for 1 h. This was recorded as electrolyte 3.

[0124] (5) Using N-methylpyrrolidone as a solvent (there is no specific requirement for the amount of the solvent, and the solvent is added until the lithium salt and the polymer are dissolved), add 0.25 g of LiTFSI and 0.75 g of polyacrylonitrile with a number average molecular weight of 10,000, stir and dissolve evenly, and record it as an electrolyte solution; wherein the sum of the mass of the lithium salt and the polyacrylonitrile accounts for 20% of the mass of the electrolyte solution;

[0125] (7) Apply electrolytes 1, 2, and 3 to the negative electrode sheet in sequence, and bake at 60° C. for 20 min in an argon atmosphere before applying the next electrolyte;

[0126] (8) Heat the electrolyte solution to 80°C, apply it on electrolyte 3, and bake it at 80°C for 20 min in an argon atmosphere;

[0127] (9) Repeat step (8) in the order of electrolytes 3, 2, and 1 to prepare a composite electrolyte containing a gradient salt concentration.

[0128] Preparation of the battery:

[0129] (10) The negative electrode sheet (graphite) coated with electrolyte obtained in step (9) and the positive electrode sheet (5 series ternary positive electrode material) are stacked to form a battery cell;

[0130] (11) packaging the battery cell obtained in step (10);

[0131] (12) The battery obtained in step (11) is formed and finally sealed.

[0132] Performance test: The prepared battery was tested on a battery test system with a test voltage of 2.8-4.2V, with a 1C200 cycle capacity retention rate of 98%, and a discharge capacity of 85% of 1C at 3C, passing the national standard GB / T 31485-2015 needle puncture test and heating test. The test results are shown in Table 1 below.

[0133] Table 1 Test results of battery performance prepared in Example 1-2

[0134]

[0135] Although the specific embodiments of the present invention are described above, it should be understood by those skilled in the art that this is only for illustration and the protection scope of the present invention is defined by the appended claims. Those skilled in the art may make various changes or modifications to these embodiments without departing from the principles and essence of the present invention, but these changes and modifications all fall within the protection scope of the present invention.

Claims

1. A composite electrolyte containing a gradient salt concentration, characterized in that: It includes a first electrolyte layer, a second electrolyte layer, and a third electrolyte layer, wherein: The second electrolyte layer is located between the first electrolyte layer and the third electrolyte layer, The first electrolyte layer includes N electrolyte layer units stacked in sequence, and the third electrolyte layer includes M electrolyte layer units stacked in sequence, wherein N and M are both natural numbers and integers, and N≥2, M≥2; According to the distance from each electrolyte layer unit to the second electrolyte layer from far to near, the N sequentially stacked electrolyte layer units in the first electrolyte layer are recorded as A1, A2, ...A N-1 , A N , the M sequentially stacked electrolyte layer units in the third electrolyte layer are denoted as A'1, A'2, ...A' M-1 , A' M ; Wherein, A1 and A'1 are respectively located in the outermost layer of the gradient salt concentration composite electrolyte; The components of the electrolyte layer units independently include a first polymer, a first organic solvent and a first lithium salt, and the concentration of the first lithium salt in each electrolyte layer unit is from A1 to A N and from A'1 to A' M All increase in sequence; wherein, the concentration of the first lithium salt in A1 and A'1 is 0.9-1.1 mol / L, and in the electrolyte layer units other than A1 and A'1, the concentration of the first lithium salt is 1-5 mol / L, and the concentration of the first lithium salt refers to the concentration of the first lithium salt relative to the first organic solvent; The ratio of the sum of the mass of the first lithium salt and the first organic solvent to the mass of the first polymer is (0.8-1.1):1; The components of the second electrolyte layer include a second polymer, a second organic solvent and a second lithium salt; wherein the sum of the masses of the second lithium salt and the second polymer accounts for 10-30%, % refers to the percentage of the sum of the masses of the second lithium salt and the second polymer to the mass of the second electrolyte layer, and the mass ratio of the second polymer to the second lithium salt is (3-4):

1.

2. The composite electrolyte containing a gradient salt concentration as claimed in claim 1, characterized in that: The types of the first lithium salt, the first polymer and the first organic solvent of each electrolyte layer unit are respectively the same as the types of the first lithium salt, the first polymer and the first organic solvent in other electrolyte layer units; and / or, the thickness of each of the electrolyte layer units is less than 100 μm; and / or, the types of the first polymer and the second polymer are independently selected from one or more of polyethylene oxide, polyvinylidene fluoride, polyacrylonitrile and polymethyl methacrylate; and / or, the first polymer and the second polymer are of the same type; and / or, the first organic solvent is selected from one or more of cyclic carbonates, linear carbonates, ethers and sulfones; And / or, the first lithium salt and the second lithium salt are represented by a chemical formula LiY, where Y - Including but not limited to: PF6 - 、CH3SO3 - 、SCN - 、BF4 - 、ClO4 - 、NO3 - 、[O3SCF2CF3] - 、AsF6 - 、AlCl4 - 、(CF3SO2)2N - 、(FSO2)2N - CF3SO3 - 、B(OC2O2)2 - 、(OC2O2)F2B - 、(C3F6SO2)(FSO2)N - or Li[(CF3SO2)(n-C4F9SO2)N]; and / or, the first lithium salt and the second lithium salt are of the same type; and / or, the concentration of the first lithium salt in A1 and A'1 is 1 mol / L; and / or, in the electrolyte layer units other than A1 and A'1, the concentration of the first lithium salt is independently 1-2 mol / L; and / or, from A1 to A N , the difference in concentration of the first lithium salt between each electrolyte layer unit is the same or different.

3. The composite electrolyte containing a gradient salt concentration as claimed in claim 2, characterized in that: The types of the first polymer and the second polymer are independently selected from one or more of polyethylene oxide, polyvinylidene fluoride and polyacrylonitrile; and / or, the first organic solvent is selected from cyclic carbonates and ethers; And / or, the first lithium salt and the second lithium salt are both (CF3SO2)2N - ; And / or, in the electrolyte layer units other than A1 and A′1, the concentration of the first lithium salt is each independently 1.2, 1.3 or 1.5 mol / L.

4. The composite electrolyte containing a gradient salt concentration as claimed in claim 2, characterized in that: The types of the first polymer and the second polymer are independently selected from polyethylene oxide or polyacrylonitrile.

5. The composite electrolyte containing gradient salt concentration as claimed in claim 2, characterized in that: The number average molecular weight of the polyethylene oxide is 50,000 to 3,000,000.

6. The composite electrolyte containing a gradient salt concentration as claimed in claim 5, characterized in that: The number average molecular weight of the polyethylene oxide is 100,000 to 3,000,000.

7. The composite electrolyte containing a gradient salt concentration as claimed in claim 6, characterized in that: The number average molecular weight of the polyethylene oxide is 300,000 to 1,000,000.

8. The composite electrolyte containing gradient salt concentration as claimed in claim 2, characterized in that: The number average molecular weight of the polyvinylidene fluoride is 10,000 to 80,000.

9. The composite electrolyte containing a gradient salt concentration as claimed in claim 8, characterized in that: The number average molecular weight of the polyvinylidene fluoride is 20,000 to 50,000.

10. The composite electrolyte containing gradient salt concentration according to claim 2, characterized in that: The number average molecular weight of the polyacrylonitrile is 8,000 to 50,000.

11. The composite electrolyte containing gradient salt concentration according to claim 10, characterized in that: The number average molecular weight of the polyacrylonitrile is 10,000 to 30,000.

12. The composite electrolyte containing gradient salt concentration according to claim 2, characterized in that: The number average molecular weight of the polymethyl methacrylate is 25,000 to 200,000.

13. The composite electrolyte containing gradient salt concentration according to claim 2, characterized in that: The cyclic carbonates include, but are not limited to, a combination of one or more of ethylene carbonate, propylene carbonate and γ-butyrolactone.

14. The composite electrolyte containing gradient salt concentration according to claim 13, characterized in that: The cyclic carbonate is propylene carbonate.

15. The composite electrolyte containing gradient salt concentration according to claim 2, characterized in that: The linear carbonates include, but are not limited to, one or more combinations of ethyl methyl carbonate, dimethyl carbonate, diethyl carbonate, methyl formate, ethyl formate, methyl acetate, ethyl acetate, n-propyl acetate, methyl propionate, ethyl propionate, n-propyl propionate, methyl butyrate and ethyl butyrate.

16. The composite electrolyte containing gradient salt concentration according to claim 2, characterized in that: The ethers are selected from one or more combinations of ethylene glycol dimethyl ether, ethylene glycol diethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether or tetraethylene glycol dimethyl ether, 1,3-dioxolane, 1,3-dioxane, 1,4-dioxane, tetrahydrofuran and 2-methyltetrahydrofuran.

17. The composite electrolyte containing gradient salt concentration according to claim 16, characterized in that: The ethers are ethylene glycol dimethyl ether or ethylene glycol diethyl ether.

18. The composite electrolyte containing gradient salt concentration according to claim 2, characterized in that: The sulfone is selected from one or more of dimethyl sulfoxide, sulfolane, and dimethyl sulfone.

19. The composite electrolyte containing gradient salt concentration according to claim 2, characterized in that: The first organic solvent is "propylene carbonate and ethylene glycol dimethyl ether" or "propylene carbonate and ethylene glycol diethyl ether".

20. The composite electrolyte containing gradient salt concentration according to claim 2, characterized in that: When the first organic solvent includes two organic solvents, the mass ratio of the two organic solvents is (4-5):(5-6).

21. The composite electrolyte containing gradient salt concentration according to claim 20, characterized in that: When the first organic solvent includes two organic solvents, the mass ratio of the two organic solvents is 4:6 or 5:

5.

22. The composite electrolyte containing gradient salt concentration as claimed in claim 2, characterized in that: The first organic solvent is propylene carbonate and ethylene glycol dimethyl ether in a mass ratio of 4:

6.

23. The composite electrolyte containing gradient salt concentration as claimed in claim 2, characterized in that: The first organic solvent is propylene carbonate and ethylene glycol diethyl ether in a mass ratio of 5:

5.

24. The composite electrolyte containing gradient salt concentration as claimed in claim 2, characterized in that: From A1 to A N or from A'1 to A' M , the difference in concentration of the first lithium salt between each electrolyte layer unit is independently selected from 0.1, 0.2 or 0.5 mol / L.

25. The composite electrolyte containing gradient salt concentration according to claim 1, characterized in that: N in the first electrolyte layer and M in the third electrolyte layer have the same value; And / or, when N and M have the same value, A in the first electrolyte layer N and A' in the third electrolyte layer M Exactly the same, A N-1 and A' M-1 Exactly the same, and so on; And / or, the values ​​of N and M are independently 2-4; And / or, in the first electrolyte layer, the ratio of "the sum of the masses of the first lithium salt and the first organic solvent" to the mass of the first polymer is (0.9-1.1):

1.

26. The composite electrolyte containing gradient salt concentration as claimed in claim 25, characterized in that: The values ​​of N and M are both 2 or 3; And / or, in the first electrolyte layer, the ratio of "the sum of the mass of the first lithium salt and the first organic solvent" to the mass of the first polymer is 1:

1.

27. The composite electrolyte containing gradient salt concentration as claimed in claim 25, characterized in that: The values ​​of N and M are both 2, the concentration of the first lithium salt in A1 and A'1 is both 1 mol / L; the concentration of the first lithium salt in A2 and A'2 is both 1.5 mol / L.

28. The composite electrolyte containing gradient salt concentration as claimed in claim 27, characterized in that: In A1, A'1, A2 and A'2, the first lithium salt is LiTFSI, the first polymer is polyethylene oxide with a number average molecular weight of 50,000, and the first organic solvent is a mixed solvent of propylene carbonate and ethylene glycol dimethyl ether in a mass ratio of 4:

6.

29. The composite electrolyte containing gradient salt concentration as claimed in claim 25, characterized in that: The values ​​of N and M are 3, the concentration of the first lithium salt in A1 and A'1 is 1 mol / L; the concentration of the first lithium salt in A2 and A'2 is 1.2 mol / L; the concentration of the first lithium salt in A3 and A'3 is 1.3 mol / L.

30. The composite electrolyte containing gradient salt concentration as claimed in claim 29, characterized in that: In A1 to A3 and A′1 to A′3, the first lithium salt is LiTFSI, the first polymer is polyacrylonitrile having a number average molecular weight of 10,000, and the first organic solvent is a mixed solvent of propylene carbonate and ethylene glycol diethyl ether in a mass ratio of 5:

5.

31. The composite electrolyte containing gradient salt concentration as claimed in claim 1, characterized in that: In the second electrolyte layer, the sum of the mass of the second lithium salt and the second polymer accounts for 15-30%, wherein % refers to the percentage of the sum of the mass of the second lithium salt and the second polymer to the mass of the second electrolyte layer; and / or, in the second electrolyte layer, the mass ratio of the second polymer to the second lithium salt is 3:1 or 4:1; And / or, in the second electrolyte layer, the second organic solvent is N-methylpyrrolidone.

32. The composite electrolyte containing gradient salt concentration as claimed in claim 31, characterized in that: In the second electrolyte layer, the sum of the mass of the second lithium salt and the second polymer accounts for 20% or 25%.

33. A method for preparing a composite electrolyte containing a gradient salt concentration, characterized in that: It includes the following steps: Mix the mixture B1, B2, ...B N-1 , B N , C, B' M , B' M-1 , ...B'2, B'1, are sequentially coated on the base layer; wherein, The mixed solutions B1 and B'1 respectively include a first lithium salt, a first organic solvent and a first polymer, wherein the concentration of the first lithium salt is 0.9-1.1 mol / L, Mixture B2, ...B N-1 , B N The difference between the mixed solution B1 and the mixed solution B2 is that the concentration of the first lithium salt is different and the concentration of the first lithium salt is different from that of the mixed solution B1. N The concentration of lithium salt is independently 1-5 mol / L. Mixture B'2, ...B' M-1 , B' M The difference between the mixed solution B'1 and B' is that the concentration of lithium salt is different and the concentration of lithium salt is different from B'1 to B' M The concentration of lithium salt is increased successively, and each of them is independently 1-5 mol / L; Said N and M are both natural numbers and integers, and N≥2, M≥2; The concentration of the first lithium salt is 1-5 mol / L, and the concentration of the first lithium salt refers to the concentration of the first lithium salt relative to the first organic solvent; The ratio of the sum of the mass of the first lithium salt and the first organic solvent to the mass of the first polymer is (0.8-1.1):1; The mixed solution C includes a second lithium salt, a second organic solvent and a second polymer; The sum of the masses of the second lithium salt and the second polymer accounts for 10-30%, % refers to the percentage of the sum of the masses of the second lithium salt and the second polymer in the mass of the mixed solution C, and the mass ratio of the second polymer to the second lithium salt is (3-4):

1.

34. The method for preparing a composite electrolyte containing a gradient salt concentration as claimed in claim 33, characterized in that: The coating thickness each time is less than 100 μm; And / or, the types of the first lithium salt, the first organic solvent and the first polymer are as described in claim 2; And / or, the types of the second lithium salt, the second organic solvent and the second polymer are as described in claim 2; and / or, the concentration of the first lithium salt in the mixed solutions B1 and B'1 is 1 mol / L; and / or, mixture B2 to B N Mixture B'2 to B' M wherein the concentration of the first lithium salt is independently 1-2 mol / L; and / or, from B1 to B N or from B'1 to B' N , the difference in concentration of the first lithium salt between each of the mixed solutions corresponding to the sequential increase is independently selected from 0.1, 0.2 or 0.5 mol / L; And / or, when N and M have the same value, B in the first electrolyte layer N and B' in the third electrolyte layer M Exactly the same, B N-1 and B' M-1 Exactly the same, and so on; And / or, the values ​​of N and M are independently 2-4; and / or, the ratio of "the sum of the mass of the first lithium salt and the first organic solvent" to the mass of the first polymer is (0.9-1.1):1; And / or, the preparation method of the mixed solution B1 comprises the following steps: dissolving the first lithium salt in the first organic solvent and then mixing with the first polymer; N and mixed solutions B'1 to B' M The preparation method of is similar to that of And / or, the sum of the mass of the second lithium salt and the second polymer in the mixed solution C accounts for 15-30%, wherein % refers to the percentage of the sum of the mass of the second lithium salt and the second polymer in the mass of the mixed solution C; And / or, the mass ratio of the second polymer to the second lithium salt in the mixed solution C is 3:1 or 4:1; And / or, the base layer is an electrode plate; and / or, after said coating, curing; And / or, the mixed solution C is coated at 75-85°C.

35. The method for preparing a composite electrolyte containing a gradient salt concentration as claimed in claim 34, characterized in that: Mixture B2 to B N Mixture B'2 to B' M wherein the concentration of the first lithium salt is independently 1.2, 1.3 or 1.5 mol / L; And / or, the values ​​of N and M are independently 2 or 3; and / or, the ratio of "the sum of the masses of the first lithium salt and the first organic solvent" to the mass of the first polymer is 1:1; And / or, the sum of the mass of the second lithium salt and the second polymer in the mixed solution C accounts for 20% or 25%; And / or, the base layer is a negative electrode plate; And / or, the mixed solution C is coated at 80°C.

36. The method for preparing a composite electrolyte containing a gradient salt concentration as claimed in claim 35, characterized in that: The negative electrode plate is graphite.

37. The method for preparing a composite electrolyte containing a gradient salt concentration as claimed in claim 34, characterized in that: The values ​​of N and M are both 2, the concentration of the first lithium salt in B1 and B'1 is both 1 mol / L; the concentration of the first lithium salt in B2 and B'2 is both 1.5 mol / L.

38. The method for preparing a composite electrolyte containing a gradient salt concentration as claimed in claim 37, characterized in that: In B1, B'1, B2 and B'2, the first lithium salt is LiTFSI, the first polymer is polyethylene oxide with a number average molecular weight of 50,000, and the first organic solvent is a mixed solvent of propylene carbonate and ethylene glycol dimethyl ether in a mass ratio of 4:

6.

39. The method for preparing a composite electrolyte containing a gradient salt concentration as claimed in claim 34, characterized in that: The values ​​of N and M are both 3, the concentration of the first lithium salt in B1 and B'1 is 1 mol / L; the concentration of the first lithium salt in B2 and B'2 is 1.2 mol / L; the concentration of the first lithium salt in B3 and B'2 is 1.3 mol / L.

40. The method for preparing a composite electrolyte containing a gradient salt concentration as claimed in claim 39, characterized in that: In B1 to B3 and B'3 to B'3, the first lithium salt is LiTFSI, the first polymer is polyacrylonitrile having a number average molecular weight of 10,000, and the first organic solvent is a mixed solvent of propylene carbonate and ethylene glycol diethyl ether in a mass ratio of 5:

5.

41. The method for preparing a composite electrolyte containing a gradient salt concentration as claimed in claim 34, characterized in that: The mixing includes stirring.

42. The method for preparing a composite electrolyte containing a gradient salt concentration as claimed in claim 41, characterized in that: The stirring was performed at room temperature.

43. The method for preparing a composite electrolyte containing a gradient salt concentration as claimed in claim 41, characterized in that: The stirring time is 1 h.

44. The method for preparing a composite electrolyte containing a gradient salt concentration as claimed in claim 34, characterized in that: The curing is carried out under an inert atmosphere.

45. The method for preparing a composite electrolyte containing a gradient salt concentration as claimed in claim 34, characterized in that: The curing is thermal curing.

46. ​​The method for preparing a composite electrolyte containing a gradient salt concentration as claimed in claim 34, characterized in that: The curing is baking.

47. The method for preparing a composite electrolyte containing a gradient salt concentration as claimed in claim 45, characterized in that: The temperature of the thermal curing is 60 or 80°C.

48. The method for preparing a composite electrolyte containing a gradient salt concentration as claimed in claim 45, characterized in that: The thermal curing time is 20 minutes.

49. A composite electrolyte containing a gradient salt concentration prepared by the method for preparing a composite electrolyte containing a gradient salt concentration as claimed in any one of claims 33 to 48.

50. A battery cell, characterized in that: The invention comprises a positive electrode, a negative electrode, and a composite electrolyte containing a gradient salt concentration as claimed in any one of claims 1 to 32 and 49.

51. The battery cell as claimed in claim 50, characterized in that The positions of the negative electrode and the positive electrode overlap each other to form a laminate, and the composite electrolyte containing a gradient salt concentration is located between the negative electrode and the positive electrode.

52. Use of a composite electrolyte containing gradient salt concentration as claimed in any one of claims 1 to 32 and 49 in a battery.

53. A lithium battery, characterized in that: It comprises the composite electrolyte containing gradient salt concentration as claimed in any one of claims 1 to 32 and 49.

Citation Information

Patent Citations

  • Gel polymer electrolyte for lithium ion battery, and preparation method thereof

    CN108365261A

  • Thermosetting electrolyte composition for lithium secondary battery, gel polymer electrolyte prepared therefrom, and lithium secondary battery comprising same

    CN112074982A